Correction: Biomimetic anti-freezing polymeric hydrogels: keeping soft-wet materials active in cold environments. Issue 12 (4th November 2020) - Jian, Yukun; Handschuh-Wang, Stephan; Zhang, Jiawei; Lu, Wei; Zhou, Xuechang; Chen, Tao
Abstract : Correction for 'Biomimetic anti-freezing polymeric hydrogels: keeping soft-wet materials active in cold environments' by Yukun Jian et al., Mater. Horiz., 2020, DOI: ; 10.1039/d0mh01029d .